Nutria trichurosis as a component of the parasitic community of the digestive tract of Myocastor coypus (Molina, 1782) - Mykhailiutenko, E.; Mykhailiutenko, S. (Scientific Progress & Innovations, 2025)
The prospects for the development of nutria farming in Ukraine indicate the presence of an open market niche for this sector, creating favorable conditions for further growth and improvement of animal husbandry technologies. One of the main factors limiting the production of nutria products in farms of various ownership forms is the lack of stable integration links between producers, processors, trade organizations, as well as the insufficient level of veterinary services. Since nutria were first introduced into Ukraine, their population has been steadily increasing. Despite the active breeding of these animals in different regions, the parasite fauna of the domestic population remains insufficiently investigated. In the natural range of nutria, more than thirty parasite species have been recorded. The aim of this study was to determine the prevalence and specific features of parasitic infections in domestic nutria. The research was conducted in farms of the Poltava region. The main indicator of infestation in these semi-aquatic rodents was the extent of invasion (EI, %). In total, 1,438 samples collected from Myocastor coypus (Molina, 1782) were examined using coproscopic methods. The results of the study showed that gastrointestinal parasitoses in domestic nutria kept in farms of the Poltava region are quite widespread (34.42 %). Analysis of data across four districts revealed that EI values ranged from 20.31 % to 37.45 %. The detected parasite fauna included Trichuris, Trichostrongylus, and Eimeria species, with trichuriosis mono-invasion being predominant, reaching 61.47 %. A total of three types of mixed infections were detected in semi-aquatic rodents infected with Trichuris myocastoris, with two-component infections found in 81.55% of nutria (EI – 9.53 %), and three-component infestations in 18.45 % of nutria (EI – 2.15 %). The findings indicate the need for the implementation of systematic prevention measures against endoparasitoses in domestic nutria, as well as for continuous monitoring of their epizootic status.